HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN KOMITMEN ORGANISASI (KASUS PT.BANK NEGARA INDONESIA (PERSERO) TBK CABANG PEKANBARU) - ", Fransiska; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Era of globalization, competition is getting tougher demands organizations that want to be able to continue to maintain the existence and success to make changes in accordance with the development of today's business world. Therefore we need leaders with transformational style. Actualization needs of employees and the articulation of a clear vision can increase organizational commitment of employees.This study aims to determine the application of transformational leadership style and how the organization's commitment to PT.Bank Negara Indonesia (Persero) Tbk Branch Pekanbaru and the relationship between the two variables in the analysis of this study using a statistical techniques and models used in this study is the product moment correlation. The results showed that there is a strong relationship between transformational leadership style and organizational commitment on PT.Bank Negara Indonesia (Persero) Tbk Branch Pekanbaru, where the results of this calculation values obtained correlation coefficient of 0.612.Thus it can be seen that the transformational leadership style has a strong relationship with the organization's commitment to the employees of PT. Bank Negara Indonesia (Persero) Tbk Branch Pekanbaru.Keywords: Transformational Leadership Style, Organizational Commitment